Analysis of chondroitin sulfate from different sources of cartilage by electrophoretically mediated microanalysis1. Issue 65 (16th July 2015) - Zhao, Ting; Zhang, Jinfu; Liu, Xiumei; Wang, Fengshan
<x xml:space="preserve">Abstract</x> An electrophoretically mediated microanalysis protocol for the determination of different chondroitin sulfate origins was developed.